ANALISIS PENGARUH LINGKUNGAN KERJA DAN MOTIVASI KERJA TERHADAP KEPUASAN KERJA PENYULUH PERTANIAN LAPANG (PPL) NON PNS DI DINAS PERTANIAN KABUPATEN SERANG PROVINSI BANTEN - Anisa, Risa; Suherman, Suherman; Gunawan, Gugun (Jurusan Agribisnis Fakultas Pertanian Universitas Sultan Ageng Tirtayasa, 2018)
Work motivation is a basic factor that affects the actions and decisions of employees in the work. While the work environment is expected to be conducive to support employee work. This study aims to determine empirically the influence of work motivation and work environment to the job satisfaction of non-civil servant field agricultural extension workers in the Serang Agricultural Service. This study used 32 non-civil servant agricultural extension workers in Serang District as the research sample. The data obtained were analyzed by using multiple regression analysis to find out whether or not the influence of variable working environment and work motivation on the job satisfaction of non-civil servant agricultural extension workers in Serang Regency. The result shows that there is positive and significant influence between work environment variable and work motivation toward job satisfaction of non civil servant agricultur field extension workers in Serang regency.